Optimization of circular coils with ferrite boxes for enhanced efficiency in wireless power transfer for electric vehicles - Soukaina Jaafari; Hamza El Hafdaoui; Khadija Ajabboune; Ahmed Khallaayoun; Esmail Ahouzi (Green Energy and Intelligent Transportation)
This study responds to global climate concerns by addressing the shift towards sustainable transportation, particularly electric vehicles. Focusing on wireless power transfer to overcome charging infrastructure challenges, the research optimizes circular coils for inductive power transfer in electric cars. Utilizing ferrite cores to enhance performance, the study employs ANSYS Electronics Suite R2-202 and the finite element method to analyze circular coils, exploring variations in turns, inner radius, air gap, and misalignment's impact on the coupling coefficient. Introducing ferrite plan cores and boxes, the research finds that ferrite boxes improve coupling efficiency by 50% and electromagnetic field strength by 300%, concentrating the field toward the center. An inequivalent design, enlarging the primary coil, demonstrates significant enhancements, achieving a coupling coefficient increase of 0.183,447 and an electromagnetic field rise of 0.000,40 ​T. Equivalent coils with ferrite boxes meet a 95% efficiency goal with a strong, narrowed field at a lower cost, while inequivalent coils excel in strengthening and centralizing the field, enhancing misalignment tolerance in distinctive ways.